Avifauna in an Urban Landscape of a Lower Ganges District Of Bangladesh: Community Structure, Seasonality, Habitat Preference and Conservation Issues (Dhaka University Journal of Biological Sciences, 2023)
A yearlong scientific study was conducted using direct field observation technique from November 2020 to October 2021 to investigate community structure, habitat preference, and conservation concerns of birds in the urban setting of Faridpur Sadar Upazila. A total of 168 species under 18 orders and 56 families were recorded and 6,551 individual of birds were counted. The order Passeriformes had the highest species richness (71 species, 42.26%) and abundance (n=3,831, 58.48%). Among the bird species, 48 species (29.58%) were migratory and the rest were resident. During the winter season, the highest number of bird species (156 species, 92.85%) and individuals (n= 2,960, 45.18%) were observed. The overall comparison of species richness and abundance for three seasons were significant. Pair-wise one-way ANOVA for species richness and abundance of birds shows significant differences between winter-rainy and summer-winter seasons.The diversity index showed the highest value in winter season. Analysis of similarity (ANOSIM) test showed a significant difference in birds communities among three-season. Among the 10 types of microhabitats surveyed, trees were the most used by the bird species (103 species, 61.31%) The highest 69 species (41.07%) were very common according to the observation status. The most abundant bird was Pycnonotus cafer with the highest relative abundance (5.15%). Bird hunting, trade, and habitat loss were the major threats for the survival of bird community in this area. Therefore, immediate initiatives are needed to implement for the conservation of bird and their habitats.Dhaka Univ. J. Biol. Sci. 31(2): 343-360, 2022 (July)